THE EFFECTIVENESS OF CITRONELLA (Cymbopogon nadrus) AROMATHERAPY ON BLOOD PRESSURE IN THE ELDERLY IN KARET, PLERET, BANTUL - Rizky Erwanto; Dwi Endah Kurniasih; Tia Amestiasih; Ametkabal Kriswento Luturmas (Universitas Respati Yogyakarta, 2022)
The elderly have hypertension due to an increase in arterial pressure. Hypertension that is not treated properly can cause complications such as stroke, coronary heart disease, diabetes, kidney failure and blindness. One of the non-pharmacological treatments for hypertension in the elderly is citronella aromatherapy. Citronella (Cymbopogon nardus) contains monoterpene alcohol such as linalool and geraniol, which function as analgesics, calm and balance stimulation, and have a vasodilator effect. Treatment of hypertension in the elderly at the research site is still limited to administering drugs (pharmacological therapy). The provision of non-pharmacological therapy to treat hypertension has not been carried out at the research site This study aimed to determine the differences in the effectiveness of citronella aromatherapy on blood pressure in hypertensive older people in Karet, Pleret, Bantul. This study used a Quasy experimental pre-post without control group design method. In addition, the researcher used the bivariate Wilcoxon signed-rank test. The results obtained are p-value of 0.00, meaning there is a significant difference in the mean value before and after the citronella aromatherapy intervention was given. Therefore, it is hoped that this intervention can be used as a reference to reduce blood pressure in the elderly who have hypertension. Keywords: Citronella Aromatherapy; Blood Pressure; Elderly